Primary ovarian pregnancy. A case report. - Yilmaz, T.; Yucel, O.; Yumbul, A.Z.; Horasan, F.; Kalfagil, M.S. (My University, 1994)
A primary ovarian pregnancy was diagnosed in a patient with intrauterine device. Primary ovarian pregnancy which is a rare form of ectopic pregnancy, was reviewed according to etiology, pathogenesis and improvements in diagnosis and therapy. In this article, our case was multiparous and used intrauterine device for 5 years. Ovarian pregnancy was diagnosed before operation. This diagnosis was verified histologically and she was treated by oopherectomy.
Keywords: Adult; Female; Humans; Intrauterine Devices; Ovary; Pregnancy; Pregnancy, Ectopic; adult; article; case report; ectopic pregnancy; female; human; intrauterine contraceptive device; ovary; pregnancy